(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The global shift toward competency-based learning has highlighted the importance of students’ ability to study and think independently. In Uzbekistan, improving history education to meet these goals remains a pressing challenge, especially in non-history majors. This article aims to develop and evaluate a methodological model for cultivating independent learning skills among university students through history instruction. A mixed-method research design was employed, including pedagogical experiments, surveys, and classroom observations conducted among undergraduate students of Karakalpak State University. The study involved 120 students divided into control and experimental groups, using specially designed historical tasks and self-assessment tools. Data were analyzed through statistical and content analysis. The proposed model significantly improved students’ abilities in critical thinking, historical analysis, independent research, and effective information processing. Students in the experimental group demonstrated a higher level of autonomy in academic performance. The study concludes that history education, when methodologically adapted, can foster independent learning among students. A structured system of task-based learning, guided reflection, and technological support plays a key role in achieving this aim.